Indien architecture, at the time of the Mamluk sultans - djairne, maamar (Journal of Social Sciences and Humanities, 2021)
Islamic architecture Is one of the Most beautiful in the world, And the pride of the Islamic heritage throughout the Muslim world, Thanks to the diversity of the building and the integration of elements of artistic and aesthetic creativity,I I studied in this article The Indian architecture and the role of the Delhi sultans The purpose of this study is to highlight the contribution of Indian Islamic architecture to the Sultans era in the consolidation of Islamic culture in the sub -continent Indian, and addressed the role of the Mamluk sultans in Indian architecture and more particularly the architecture and construction of mosques. Finally, I came to some of the most important results: -the role played by mosques in spreading the religious and cultural influence of Muslims inside and outside the country.- Creation and development of schools